Nevirapine-induced Stevens-Johnson syndrome in children living with HIV in South Africa - Jacques D. du Toit; Koot Kotze; Helene-Mari van der Westhuizen; Taryn L. Gaunt (AOSIS, 2021)
Background: Although adverse drug reactions resulting from the use of nevirapine (NVP) are well described in adults (estimated frequency of 6% - 10%), it has previously been considered less common in children (0.3% - 1.4%). Stock-outs of antiretroviral agents occur frequently in South Africa and result in interruptions in therapy and drug substitutions. Objectives: To report on a case series of paediatric patients who suffered cutaneous drug reactions to NVP at rates not previously described in children. Method: We describe a retrospective observational case series of six children living with HIV who developed Stevens-Johnson Syndrome (SJS) following exposure to NVP because of a prolonged stock-out of efavirenz 200 mg tablets in South Africa. Results: Of the 392 paediatric patients receiving antiretroviral therapy at the institution, 172 were affected by the efavirenz stock-out. Of these, 85 children were changed to NVP of which six developed NVP-induced SJS (7.1% incidence rate). The median time between initiating NVP and developing symptoms was 27 days (range 12-35 days). All patients responded well to NVP cessation and symptomatic treatment. One patient was referred for specialist care. Two patients were successfully rechallenged with efavirenz after developing SJS and three continued lopinavir/ritonavir. Conclusions: This is the second largest case series of NVP-induced SJS in children to date and raises the possibility that the incidence of SJS in children may be higher than previously described. Further research is required to explore the risk factors associated with NVP-induced SJS in children. This case series highlights the negative impact of drug stock-outs on patient health outcomes.